Effect of seed treatment on the germinating capacities and standing plant density - Гончар, Л. М.; Щербакова, О. М. (Scientific Progress & Innovations, 2016)
Studies in stationary experiment EP «Agronomic Research Station» during 2012–2014 years in typical black soil found that treating seeds by nodule bacteria and molybdenum solution is an effective reception for improving chickpea seed germination by redox processes in the seeds. We established that survival chickpea plants during the growing season considerably depend on weather conditions of growing and preplant processing of seeds. Inoculation of seed and its processing by molybdenum colloidal solution improves plant resistance to stress and survival of plants during the growing season culture in 6,5–10,5 %, inoculation without the use of colloidal solution of molybdenum – by only 1,9–2,5 %.